University of destruction : your game plan for spiritual victory on campus - Wheaton, David, 1969- (Minneapolis, Minn. : Bethany House Publishers, 2005)
'With a conversational style, author David Wheaton explores the three pillars of peril--sex, drugs, and rebellion--most often encountered by college students. He then offers students advice on developing a game plan to avoid the spiritual pitfalls'--Provided by publisher
Includes bibliographical references (p. 173)
Keywords: College students -- Religious life; Sex -- Religious aspects -- Christianity; Drugs -- Religious aspects -- Christianity; Conflict of generations